2016
DOI: 10.1155/2016/9353275
|View full text |Cite
|
Sign up to set email alerts
|

Nanosilica and Polyacrylate/Nanosilica: A Comparative Study of Acute Toxicity

Abstract: We compared the acute toxicity of nanosilica and polyacrylate/nanosilica instillation in Wistar rats (n = 60). Exposure to nanosilica and polyacrylate/nanosilica showed a 30% mortality rate. When compared with saline-treated rats, animals in both exposure groups exhibited a significant reduction of PO2 (P < 0.05) at both 24 and 72 hr. after exposure. Both exposure groups exhibited a significant reduction of neutrophils in arterial blood compared to saline controls (P < 0.05) 24 hr. after exposure. The levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Due to the inappropriate workplace conditions and the lack of protective gear, the degree to which nanoparticle exposure was responsible for the aforementioned observations was debatable. That being said, the findings were replicated in a rat model of intratracheal instillation of the same polyacrylate/nanosilica, further supporting the notion that some inhaled nanoparticles may be associated with pleural pathology (i.e., effusions, inflammation, fibrosis) (Niu et al, 2016 ; Zhu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 54%
“…Due to the inappropriate workplace conditions and the lack of protective gear, the degree to which nanoparticle exposure was responsible for the aforementioned observations was debatable. That being said, the findings were replicated in a rat model of intratracheal instillation of the same polyacrylate/nanosilica, further supporting the notion that some inhaled nanoparticles may be associated with pleural pathology (i.e., effusions, inflammation, fibrosis) (Niu et al, 2016 ; Zhu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 54%
“…[6,8,30,31] Previous studies have indicated that SiNPs exposure induces pleural and pericardial effusion, pulmonary brosis, and granuloma in rats, which is similar to the symptoms observed in exposed workers. [9,10,32] However, the underlying pathological mechanism of SiNPs remains unknown. The results of this study show that SiNPs cause increased pulmonary in ammation and permeability, LEC damage, and pulmonary lymphangiogenesis and remodeling by activating the VEGFC/D-VEGFR3 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The main advantages of using colloidal n-SiO 2 are high volume to surface area (7,8) and no harm to humans. The powdered form of n-SiO 2 gives better results than the colloidal form but is very harmful to human health (9). The colloidal n-SiO 2 also has excellent dispersion properties and can be distributed evenly throughout the mix if applied correctly.…”
Section: Introductionmentioning
confidence: 99%